Designing a Patient Portal for Patient-Centered Care: Cross-Sectional Survey - Van den Bulck, Steve Alfons (J Med Internet Res, 2018)
BACKGROUND: In recent literature, patient portals are considered as important tools for the delivery of patient-centered care. To date, it is not clear how patients would conceptualize a patient portal and which health information needs they have when doing so. OBJECTIVE: This study aimed (1) to investigate health information needs, expectations, and attitudes toward a patient portal and (2) to assess whether determinants, such as patient characteristics, health literacy, and empowerment status, can predict two different variables, namely the importance people attribute to obtaining health information when using a patient portal and the expectations concerning personal health care when using a patient portal. METHODS: We conducted a cross-sectional survey of the Flemish population on what patients prefer to know about their digital health data and their expectations and attitudes toward using a patient portal to access their electronic health record. People were invited to participate in the survey through newsletters, social media, and magazines. We used a questionnaire including demographics, health characteristics, health literacy, patient empowerment, and patient portal characteristics. RESULTS: We received 433 completed surveys. The health information needs included features such as being notified when one’s health changes (371/396, 93.7%), being notified when physical parameters increase to dangerous levels (370/395, 93.7%), observing connections between one’s symptoms or diseases or biological parameters (339/398, 85.2%), viewing the evolution of one’s health in function of time (333/394, 84.5%), and viewing information about the expected effect of treatment (349/395, 88.4%). Almost 90% (369/412) of respondents were interested in using a patient portal. Determinants of patients’ attachment for obtaining health information on a patient portal were (1) age between 45 and 54 years (P=.05); (2) neutral (P=.03) or interested attitude (P=.008) toward shared decision making; and (3) commitment to question physicians’ decisions (P=.03, R(2)=0.122). Determinants of patients’ expectations on improved health care by accessing a patient portal were (1) lower education level (P=.04); (2) neutral (P=.03) or interested attitude (P=.008) toward shared decision making; and (3) problems in understanding health information (P=.04; R(2)=0.106). CONCLUSIONS: The interest in using a patient portal is considerable in Flanders. People would like to receive alerts or some form of communication from a patient portal in case they need to act to manage their health. Determinants such as education, attached importance to shared decision making, difficulties in finding relevant health information, and the attached importance in questioning the decisions of physicians need to be considered in the design of a patient portal.